2014
DOI: 10.1158/1078-0432.ccr-13-1942
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Harnessing E2F1 Regulation for Prosenescence Therapy in p53-Defective Cancer Cells

Abstract: Induction of terminal proliferation arrest, senescence, is important for in vivo tumor-suppressive function of p53. Moreover, p53-mutant cells are highly resistant to senescence induction by either oncogenic signaling during cellular transformation or in response to different therapies. Senescence resistance in p53-mutant cells has been attributed mostly to inhibition of the checkpoint function of p53 in response to senescence-inducing stress signals. Here, we review very recent evidence that offers an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…2 ). These findings coincide with known effects of other MDM2 inhibitors on the p53/MDM2/ PUMA/p21/pRb/E2F1 cascade [12,45,46] . Further p53-mediated downstream effects alter the p53/MDM2/ PUMA/p21/pRb/E2F1 cascade and mediate the antitumoral effects of MDM2 inhibitors [12,35,46] .…”
Section: The Mdm2 Inhibitor Nvp-cgm097 Increases the Expression Of P5supporting
confidence: 88%
See 1 more Smart Citation
“…2 ). These findings coincide with known effects of other MDM2 inhibitors on the p53/MDM2/ PUMA/p21/pRb/E2F1 cascade [12,45,46] . Further p53-mediated downstream effects alter the p53/MDM2/ PUMA/p21/pRb/E2F1 cascade and mediate the antitumoral effects of MDM2 inhibitors [12,35,46] .…”
Section: The Mdm2 Inhibitor Nvp-cgm097 Increases the Expression Of P5supporting
confidence: 88%
“…These findings indicate that NVP-CGM097 is a highly specific MDM2 inhibitor increasing p53, PUMA, and p21 expression and interacting with the MDM2/p53/PUMA/p21/Rb/E2F1 cascade [46] . CDK4/6-cyclin D-or CDK2-cyclin E-mediated phosphorylation of Rb protein results in its inactivation, dissociation of the pRb/E2F complex, and repression of E2F transcription factors [46,80] . Double knockout experiments in Men1+/-Cdk4-/-mice indicate that CDK4 is essential for NET development [81] .…”
Section: Discussionmentioning
confidence: 78%
“…Its protein expression level is increased in many human cancers such as hepatocarcinomas, digestive adenocarcinomas and ovarian cancers, and its downregulation in p53- and RB-compromised cancer cells can trigger their senescence. 1 Further understanding of E2F1 expression regulation would help to develop strategies targeting this protein in cancer cells.…”
mentioning
confidence: 99%
“…Furthermore, Ror2 is expressed highly in embryonic tissues that contain abundantly proliferating cells, indicating that E2F1‐induced transcriptional activation of Ror2 might also be involved in the expression of Ror2 in these proliferating cells during embryogenesis. E2F1 is also activated strongly in cancer cells through various mechanisms, including activation of oncogenes and inhibition of tumor suppressor genes . It has been shown that Ror2 is expressed highly in lung adenocarcinoma cells harboring p53 loss‐of‐function mutations and in human papillomavirus (HPV)‐positive head and neck squamous cell carcinoma, where HPV oncogenic protein E7 represses Rb .…”
Section: Discussionmentioning
confidence: 99%